Analysis of The "Ruangguru" Application in Improving Children's Creativity in The Era of Covid 19 Pandemic - Munawwir, A; Nerizka, Dea (International Journal of Educational Research & Social Sciences, 2021)
The plague that initially only existed in China has now turned into grains of dust blown away by the wind, and has spread all over the world, including Indonesia. A vaccine for the virus called corona or what is known as covid 19 has not been found, which has eaten a lot of people, from those who were only infected to those who breathed their last. The plague like this makes all countries in the world forced to take preferential steps to prevent its spread that is increasingly widespread. One of the steps taken by the Indonesian government is social distancing. Such restrictions in turn also affect the education sector, in which all schools and campuses are closed. Of course, educational activists will not let the teaching and learning process take off. Online schools are one of the solutions taken by many educational units in Indonesia. Besides online schools, the ruangguru tutoring platform which provides a lot of material is also used as a place to study. This study will further analyze the role of the ruangguru in developing children's creativity in this pandemic era. The research model is a sentiment analysis. The results showed that positive comments about ruangguru reached 430, negative comments reached 57, and mediocre comments reached 14.